Respuesta :
Balanced equation:
Al2(SO4)3 +3 Ca(OH)2 ---> 2Al(OH)3 + 3CaSO4?
Check:
Left side: Al:2; [SO4]: 3; Ca: 3; [OH] 3*2 = 6
Rigth side: Al: 2; [OH]: 2*3 = 6; Ca:3; [SO4]: 3
Mole ratio of Ca(OH)2 : Al (OH)3
3 moles of Ca(OH)2: 2moles of Al(OH)3 = 3:2
Answer: Option B.
Al2(SO4)3 +3 Ca(OH)2 ---> 2Al(OH)3 + 3CaSO4?
Check:
Left side: Al:2; [SO4]: 3; Ca: 3; [OH] 3*2 = 6
Rigth side: Al: 2; [OH]: 2*3 = 6; Ca:3; [SO4]: 3
Mole ratio of Ca(OH)2 : Al (OH)3
3 moles of Ca(OH)2: 2moles of Al(OH)3 = 3:2
Answer: Option B.